ACTIVITIES TO ENCOURAGE SPEAKING ENGLISH AS A FOREIGN ANGUAGE (A CASE STUDY OF ENGLISH CLUB PARTICIPANTS IN STMIK PROVISI SEMARANG) - qorinta shinta (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract Speaking is one of the four macro skills to be developed as means of effective communication in both first and second language learning contexts. In the English as a Foreign Language pedagogy environment, how to increase speaking competence and confidence for undergraduate students tends to be an important question. This concern led to a qualitative research. The findings indicated that confidence and mastery of gramar andvocabulary, the teacher’s roles as prompter and feedback provider, and speaking activities such as information gap and role play were the key aspects that encourage students to communicate in English class better.